Postoperative results of minimally invasive direct coronary artery bypass procedure in 234 patients - Monsefi, Nadejda; Alaj, Eissa; Sirat, Sami; Bakhtiary, Farhad (Frontiers in Cardiovascular Medicine, 2023)
The popularity of minimally invasive approach in cardiac surgery is increasing. Minimally invasive direct coronary artery bypass (MIDCAB) is a less traumatic surgical technique, offers a good solution for revascularisation of isolated left anterior descending (LAD), and is also an option for hybrid revascularisation procedure in multi-vessel disease. From 2017 to 2021 234 patients underwent MIDCAB procedure in our heartcenter. 27% were female. The majority of patients had two or three vessel disease (74%). Patients´ mean age was 66±12 years. The left internal mammary artery (LIMA) was anastomosed to the left anterior descending via left minithoracotomy approach in all patients. Multi-vessel MIDCAB (MV-MIDCAB) with two anastomoses (additional saphenous vein graft as T-graft to LIMA) was performed in 35 patients (15%). Mean operation time was 2.3±0.8 hours. The 30-day mortality was 1.7% (n=4). The applied amount of packed red blood cells (pRBC) was 0.4±0.8 units. The average intensive care unit stay (ICU) was 1±1.2 days. We observed wound infections in three patients (1.3%) postoperatively. One patient (0.4%) presented with a minor stroke postoperatively. Myocardial infarction was observed in two patients (0.9%) who underwent coronary re-angiography perioperatively and stent therapy of the right coronary artery. MIDCAB for selected patients with proximal LAD lesions or as a hybrid procedure in multi-vessel disease is a safe procedure with a low 30-day mortality and good clinical outcome. Intra- and perioperative application of pRBC´s and ICU stay are low. The trauma and incision are small with a good cosmetic result. However, long-term clinical follow up data are necessary to strengthen our thesis.